2018
DOI: 10.1101/443036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The whale shark genome reveals how genomic and physiological properties scale with body size

Abstract: The endangered whale shark (Rhincodon typus) is the largest fish on Earth and is a long-lived member of the ancient Elasmobranchii clade. To characterize the relationship between genome features and biological traits, we sequenced and assembled the genome of the whale shark and compared its genomic and physiological features to those of 81 animals and yeast. We examined scaling relationships between body size, temperature, metabolic rates, and genomic features and found both general correlations across the ani… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Despite their large body size, endangered status, and appeal to both scientists and the general public, relatively little is known about their biology [8][9][10] . Due to its phylogenetic position among vertebrates, the scarcity of shark genomes, and its unique biology, the whale shark genome can be used to address questions related to vertebrate genome evolution 11,12 , the relationship of gene evolution in sharks and unique shark traits 11,12 , as well as the evolution of gigantism 13 . As expected, Read et al found that whale shark genome was most closely related among sequenced fish genomes (at the time) to Callorhinchus .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their large body size, endangered status, and appeal to both scientists and the general public, relatively little is known about their biology [8][9][10] . Due to its phylogenetic position among vertebrates, the scarcity of shark genomes, and its unique biology, the whale shark genome can be used to address questions related to vertebrate genome evolution 11,12 , the relationship of gene evolution in sharks and unique shark traits 11,12 , as well as the evolution of gigantism 13 . As expected, Read et al found that whale shark genome was most closely related among sequenced fish genomes (at the time) to Callorhinchus .…”
Section: Introductionmentioning
confidence: 99%
“…More recent work has focused upon further sequencing, assembling, and analyzing of the whale shark nuclear genome 6,11,13 . Hara et al 11 generated novel elasmobranch genome assemblies for the brown-banded bamboo shark ( Chiloscyllium punctatum ) and cloudy catshark ( Scyliorhinus torazame ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation